Phytoplankton Based Trophical State of the Tuok Tonga Lake in the Buluh Cina Village, Kampar District, Riau Province - Mujahidah Ulya; Madju Siagian; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractTypes and abundanceof phytoplankton can be used to determined the trophic state of water.To understand the types and abundances of phytoplankton present in the Tuok Tonga Lake, a research has been conducted in June-July 2019. There were three sampling points, namely in the inlet, in the middle of the lake and in the end of the lake. In each sampling point, water was sampled from the surface and 2 Secchi depth. Samplings were conducted 3 times, once/week. Water quality parameters measured were temperature, transparency, depth, dissolved oxygen, CO2, pH, nitrate and phosphate contents. Results shown that there were 43 species of phytoplankton that were belonged to 5 classes, namely Bacillariophyceae (10 species), Chlorophyceae (24 species), Cyanophyceae (4 species), Euglenophyceae (4 species) and Cryptophyceae (1 species). The phytoplankton abundance in the Tuok Tonga Lake was 59,462-129,908 cells/L. The most common type of phytoplankton present was Monoraphodium sp. Results shown that the temperature was 29.7-31.7oC, transparency was 61.7-62.7 cm, depth was 125-284 cm, pH was 5, dissolved oxygen was 3.4-5 mg/L, CO2 was 5.3-14.7 mg/L, nitrate was 0.02-0.08 mg/L, phosphate was 0.03-0.15 mg/L and pH was 5. Based on the type and abundance of phytoplankton present, it can be concluded that the Tuok Tonga Lake can be categorized as mesotrophic. Keywords: Kampar River, Oxbow Lake, Mesotrophic, Phytoplankton abundance